2014
DOI: 10.1071/zo13103
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and histology of the uropygial gland in Antarctic birds: relationship with their contact with the aquatic environment?

Abstract: The uropygial gland is morphologically different in diverse bird species. This gland was macroscopically and microscopically examined in penguins, storm petrels and skuas. In all the studied species, the gland showed a connective tissue capsule and one papilla. A negative relationship was observed between the relative glandular mass and the body mass, being highest in petrels (small glands) and lowest in penguins (large glands). Birds that spend much time in water (penguins) have gland characteristics related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 20 publications
2
28
0
2
Order By: Relevance
“…The general histological description is also similar to other birds, where the adenomers are divided into different strata, from basal or germinative stratum to degenerative stratum, and the presence of a capsule and stroma of dense connective tissue (Lucas and Stettenheim 1972;Jacob (Chiale et al 2014(Chiale et al , 2015; although Hou (1928) denied the presence of elastic fibres in the uropygial gland, more recently, Kozlu et al (2011) denied the presence of reticular fibres as part of the connective tissue in the uropigial gland of the white stork Ciconia ciconia. Birds with less contact with water have a large primary chamber, whereas aquatic birds such as penguins or skuas only have secondary chambers that lead directly to the external openings in the papilla (Chiale et al 2014). Birds with less contact with water have a large primary chamber, whereas aquatic birds such as penguins or skuas only have secondary chambers that lead directly to the external openings in the papilla (Chiale et al 2014).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The general histological description is also similar to other birds, where the adenomers are divided into different strata, from basal or germinative stratum to degenerative stratum, and the presence of a capsule and stroma of dense connective tissue (Lucas and Stettenheim 1972;Jacob (Chiale et al 2014(Chiale et al , 2015; although Hou (1928) denied the presence of elastic fibres in the uropygial gland, more recently, Kozlu et al (2011) denied the presence of reticular fibres as part of the connective tissue in the uropigial gland of the white stork Ciconia ciconia. Birds with less contact with water have a large primary chamber, whereas aquatic birds such as penguins or skuas only have secondary chambers that lead directly to the external openings in the papilla (Chiale et al 2014). Birds with less contact with water have a large primary chamber, whereas aquatic birds such as penguins or skuas only have secondary chambers that lead directly to the external openings in the papilla (Chiale et al 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Birds with less contact with water have a large primary chamber, whereas aquatic birds such as penguins or skuas only have secondary chambers that lead directly to the external openings in the papilla (Chiale et al 2014). Other studies found PAS positivity in the basal stratum and the uropygial secretion but in a homogeneous pattern, showing no division between a glycogen and sebaceous zones (Montalti et al 2001;Chiale et al 2014Chiale et al , 2015. The histochemistry and lectin histochemistry analysis showed a variety of glycoconjugates as part of the uropygial gland, highlighting the complexity of the chemical composition of secretions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uropygial (oil or preen) gland is a paired structure found at the base of the tail in most bird species (Johnston, ), and it is particularly large in many aquatic bird species (Stettenhein, ; Montalti and Sakibián, ; Vincze et al, ). It has been proposed that the bird's level of interaction with water appears to affect the size of the gland: several fully aquatic birds have larger gland than semi aquatic birds (Møller et al, ; Chiale et al, ), though there is evidence that shows otherwise, instead suggesting that the difference may be more chemical in nature (Montalti and Sakibián, ). Some recent studies connect this ecological size disparity to a putative role as an accessory to the immune system (Møller et al, ).…”
mentioning
confidence: 99%